Are maldanids from deep-sea reduced habitats closely related? Implications of a new wood-fall species of Nicomache from the South China Sea - Wang, Yueyun; Zhou, Yadong; Zhang, Dongsheng; Wang, Chunsheng (Frontiers in Marine Science, 2024)
A new wood-fall associated maldanid discovered at 2321 mdepth in the South China Sea. is here morphologically and molecularly described as Nicomache tigilli sp. nov. The new species is characterized by having 21 chaetigers, a prostomium rounded anteriorly, an arched cephalic keel, anterior ends of nuchal grooves curved outwards, 3-6 acicular spines on chaetiger 1-3, notopodia with simply long and narrow capillary chaetae, and an anal funnel with triangular, unequal-sized anal cirri. Our molecular analyses of the genus Nicomache, encompassing COI, 16S, 18S, and 28S genes supports erecting the new species, which appear phylogenetically closely related to the other species of the genus from reduced habitats.Maldanidae, a sedentary tube-building polychaete family known as bamboo worms, is widely distributed from the intertidal to the deep sea and from sandy beaches to muddy sediments, including chemosynthetic environments (De